Interleukin-3-mediated regulation of β-catenin in myeloid transformation and acute myeloid leukemia. Issue 1 (5th March 2014) - Sadras, Teresa; Perugini, Michelle; Kok, Chung H; Iarossi, Diana G; Heatley, Susan L; Brumatti, Gabriela; Samuel, Michael S; To, Luen B; Lewis, Ian D; Lopez, Angel F; Ekert, Paul G; Ramshaw, Hayley S; et al.
Abstract : IL-3 activates β-catenin in Hox-transformed myeloid cells, and primary AML samples, presenting a novel axis for targeted inhibition of β-catenin in some patients with AML. ABSTRACT: Aberrant activation of β-catenin is a common event in AML and is an independent predictor of poor prognosis. Although increased β-catenin signaling in AML has been associated with oncogenic translocation products and activating mutations in the FLT3R, the mechanisms that activate β-catenin in AML more broadly are still unclear. Here, we describe a novel link between IL-3 signaling and the regulation of β-catenin in myeloid transformation and AML. In a murine model of HoxB8 and IL-3 cooperation, we show that β-catenin protein levels are modulated by IL-3 and that Cre-induced deletion of β-catenin abolishes IL-3-dependent growth and colony formation. In IL-3-dependent leukemic TF-1.8 cells, we observed increased β-catenin protein levels and nuclear localization in response to IL-3, and this correlated with transcriptional induction of β-catenin target genes. Furthermore, IL-3 promoted β-catenin accumulation in a subset of AML patient samples, and gene-expression profiling of these cells revealed induction of WNT/β-catenin and TCF4 gene signatures in an IL-3-dependent manner. This study is the first to link β-catenin activation to IL-3 and suggests that targeting IL-3 signaling may be an effective approach for the inhibition of β-catenin activity in some patients with AML.